Application of a new scan body for face‐driven fixed prosthetics. Issue 1 (25th August 2021) - Otawa, Naruto; Aoki, Tsukasa; Sumida, Tomoki; Yanagi, Tsukasa; Kido, Hirofumi
Abstract: Objective: The current method of digitally designing dental prostheses mainly focuses on intra‐oral soft and hard tissues, although the harmony of the facial soft tissue and the prosthesis is crucial, especially for esthetics. Here, we introduce a new method of digitally designing dental prostheses using a new device that generates a virtual patient and incorporates facial features into the prosthetic design. Materials and methods: A new extra‐oral scan body for facial scanning was designed and developed. A definitive edentulous maxilla implant cast with four extra‐oral scan bodies (regions: maxillary left and right lateral incisors, maxillary left and right premolars) was placed in the mouth of a dental mannequin. The dental mannequin was scanned with and without the extra‐oral scan bodies. For reference data, an impression of the maxilla was taken and scanned with a laboratory scanner. By superimposing each acquired data, a virtual patient was generated, and the spatial location of the abutments relative to the face was clarified. Identifying the accurate location of the abutments enabled to design face‐driven dental prosthesis. Results: Based on the color‐coded deviation map created by the data acquired from conventional and extra‐oral scan bodies, the divergence of the two data was mostly within 0.1 mm, which proves that the extra‐oral scan bodies were as accurate as conventional scan bodies. Therefore, the facial scan data and the scan data of the oral cavity were successfully superimposed, which allowed to generate a virtual patient to design face‐driven prosthesis. Conclusion: The new method is effective for designing high‐quality face‐driven prostheses, especially when treating a patient with a full‐arch implant‐fixed prosthesis.